Competitive Wetting: A New Approach to Prevent Liquid Penetration through Porous Materials with Superior Synergistic Effect. Issue 49 (8th October 2021) - Ding, Jie; Kearney, James; Wang, Hongxia; Tian, Tongfei; Rutledge, Gregory C.; Lin, Tong; Wang, Xiaolin
Abstract: Blocking liquid penetration in porous materials is a key function for several applications including chemical protective clothing (CPC), wound healing, and hygiene products. Enormous efforts are made to prevent liquid penetration through porous media by the modification of materials. CPC is used as an example to demonstrate the effect of the synergistic effect on liquid penetration. A common strategy to achieve liquid protection is the use of liquid‐repellent surfaces with the aid of a liquid absorption liner layer. However, this strategy demonstrates limited success for low surface energy liquids. Herein, a novel approach is reported to prevent the permeation of liquid across porous materials by a synergistic effect. Both fabrics are individually susceptible to be wetted by low surface tension liquids. However, when they are assembled, they can prevent low surface tension liquids from penetrating because of the wettability gap between the two fabrics. The fabric assembly demonstrates an increase in the liquid prevention capacity by 70–1000 times compared with a commercial CPC material. This novel synergistic effect may offer a breakthrough in the development of various applications including protective clothing baby nappies, hygiene products, food preparation, soil water retention, and sporting/camping/ski equipment and clothing. Abstract : A novel approach to prevent the permeation of liquid across porous materials by a synergistic effect is reported. Both fabrics are individually susceptible to be wetted and penetrated by low surface tension liquids. However, when they are assembled, they can prevent the low surface tension liquids from penetrating because of the wettability gap between the two fabrics.